2017
DOI: 10.1371/journal.pone.0171277
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Genotype 4 Swine Hepatitis E Virus in Systemic Tissues in Cross-Species Infected Rabbits

Abstract: Increasing evidence demonstrates that hepatitis E virus (HEV) can be transmitted across species. According to previous reports, swine HEV has two genotypes, genotype 3 and 4, and both can infect humans by the fecal-oral route. Thus, it is crucial for the control of HEV zoonotic transmission to evaluate the dynamics of viral shedding and distribution in different tissues during cross-species infection by HEV. In this study, rabbits were infected with genotype 4 swine HEV by the intraperitoneal route. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
(75 reference statements)
2
21
0
Order By: Relevance
“…Rabbits inoculated with human HEV-3 showed poor infectivity with only seroconversion, but not viral shedding [23]. Other studies demonstrated that rabbits infected with human and swine HEV-4 strains could induce viral shedding and seroconversion, similar to the results presented here [23,24,34].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Rabbits inoculated with human HEV-3 showed poor infectivity with only seroconversion, but not viral shedding [23]. Other studies demonstrated that rabbits infected with human and swine HEV-4 strains could induce viral shedding and seroconversion, similar to the results presented here [23,24,34].…”
Section: Discussionsupporting
confidence: 85%
“…Their ALT and AST levels remained in the normal ranges. However, elevation of ALT was observed in rabbits infected with both human and swine HEV-4 strains [23,24,34]. These discrepancies could be attributed to differences in the virulence and dose of viruses used in the different studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several in vivo models including rabbit and swine have isolated HEV genotype 4 that was shed in saliva in the salivary glands and tonsils (Williams et al., ; Wu et al., ). Furthermore, negative‐stranded HEV RNA has also been detected in the salivary glands, suggesting that there may be extrahepatic sites of replication (Williams et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports had demonstrated rabbits to be susceptible to experimental infection by genotype 4 human and pig HEV isolates [23][24][25], prompting the use of rabbits as an animal model for studying HEV pathogenicity. Importantly, a rabbit model has many advantages [23,26], including lower cost and easier manipulation as compared with large animal models.…”
Section: Introductionmentioning
confidence: 99%